UPAYA PENINGKATAN KINERJA PETUGAS REGISTER KELOMPOK SENI DI DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN TEMANGGUNG - Hambriyanto Hambriyanto; Syeh Assery (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study aims to identify the factors causing the performance of Art Group Register officers at the Culture and Tourism Office of Temanggung Regency to not reach the target and to formulate efforts to improve the performance of Art Group Register officers. This research method is descriptive qualitative research. Research data obtained from interviews, documentation and observation. The factors that caused the performance of registrar officers not to reach the target were very limited human resources, inadequate facilities and infrastructure. Efforts made to improve performance include adding existing human resources, improving facilities and infrastructure, providing training on public services, providing outreach to register applicants, making new innovations in register services, namely by making digital forms.